Who Are Malaysia’s Bicycle Tourists? An Exploratory Analysis of Their Key Features - Zamzari, Asy-Syifa’; Saad, Mazni; Bawazir, Mohammed A. (IIUM Press, 2025)
This paper dives into the new phenomenon of bicycle tourism in Malaysia by outlining the major demographic and behavioural characteristics of bike tourists. This study is a response to the increased popularity of cycling (which seems to be going even higher due to the COVID-19 pandemic) and fills the gap in empirical evidence regarding the cycling tourism market in Malaysia. A quantitative research method with a snowball sampling technique was used, providing online survey information to 206 active bicycle riders who were surveyed online through the Malaysia Cycling Community. Results indicate that the Malaysian bicycle tourists are overwhelmingly young adult males, well educated, and aged between 18 and 27 years. The majority upbike on recreational road rides once per week (mainly with friends) and like short trips that are not overnight. Their spending habits should be indicative of the idea that they seek value products when it comes to cycling. The insights can provide useful recommendations to tourism planners, policymakers, and local businesses in the effort to optimize infrastructure, stimulate sustainable tourism attractions, and tailor services to the special needs of the swelling demographic. The paper is relevant to the academic literature on niche tourism as well as to the informed development of the bicycle tourism industry in Malaysia.